Professional profile of a competency-based university graduate in the era of virtuality - Tridente Rincón, Anna María (Encuentro Educacional, 2021)
An adequate curricular design translates into the success or failure of an individual, hence the importance of an updated study on the qualities and basic performances that all university graduates must possess before entering the field of work which, in addition, will also be very useful to function in the current information and knowledge society. The objective of this research was to investigate the technical, technological, participatory and communicative competences that a university graduate must possess in the era of virtuality in order to allow individuals to successfully face the labor field of their choice. Among the theoretical contributions to address this investigation, are those of Basurto et al. (2020); Sandí and Sanz(2018); Fonseca and Gamboa (2017); Argudín (2015); Alles (2015), among others. The research is framed in a documentary design with a descriptive level, through the search, analysis, interpretation and characterization of information obtained from different printed and digital sources. The study led to the selection of a series of competencies necessary for efficient, successful, and productive work performance in today’s times of social distancing and virtuality. These results can be applied to different areas of knowledge, such as education, engineering, mathematics, social sciences. Likewise, they can be relevant for any university institution that wishes to develop, deepen, and project the capacities of its graduates.